Responses of South Island Hector's dolphins (Cephalorhynchus hectori hectori) to vessel activity (including tourism operations) in Akaroa Harbour, Banks Peninsula, New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Marine Biology at Massey University, Auckland, New Zealand - Martinez, Emmanuelle; Martinez, Emmanuelle (Massey University, 2010)
For over 25 years, tour operators have been undertaking view and swim-with-dolphin trips in Akaroa Harbour off Banks Peninsula, east coast South Island, New Zealand. Following the international exponential growth in the commercial dolphin-based tourism industry, Akaroa Harbour is now a key eco-tourism destination in New Zealand with 32 daily permitted trips targeting Hector’s dolphin (Cephalorhynchus hectori hectori). Such a high number of trips is of particular concern given that this species is not only endemic but also endangered. Our current understanding of the effects of tourism activities on Hector’s dolphins in Akaroa Harbour is far from satisfactory. To ensure the sustainability of the economically-important and rapidlygrowing dolphin-based tourism industry, there is an urgent need for sound scientific evidence on which to base management decisions. One of the challenging issues with the assessment of tourism impacts is the lack of baseline data. Prior to beginning the evaluation of the effects of disturbance on this population, data relating to the occurrence and demographics of Hector’s dolphins, as well as vessel traffic in Akaroa Harbour, were collected from land-based platforms during three consecutive austral summers (November and March), commencing in 2005. Examination of Sighting Per Unit Effort (here number of dolphin sightings per hour) and the dolphin fine-scale spatial distribution confirmed an inshore-offshore migration and, in the case of the latter, higher density patterns between the Kaik hills and the harbour entrance. However, no specific area was associated with a particular behaviour or nursery groups. The majority of groups consisted of adults only (91.2%, n = 2,000) and comprised mainly 2-5 individuals (83.2%). Group size varied with behaviour, being larger when socialising. Activity budgets within two outer bays were very comparable to Akaroa Harbour, except for socialising. In the harbour, Hector’s dolphins only spent a small proportion (14%) of their day (0600-1800 hr) in the absence of vessels. Vessel traffic in the harbour consisted mainly of recreational vessels (72.9%) although commercial vessels represented 70.4% of observed encounters and interacted twice as long with the dolphins. No displacement was evident and as a result, Hector’s dolphins might compensate for high vessel traffic levels by adjusting their behavioural budget. To determine the effects of tourism activities on Hector’s dolphins’ behavioural budget, focal-group follows using a scan sample methodology were conducted from land-based stations and analysed using Markov chain models (n = 330 sequences). Vessel presence affected the activity budget of Hector’s dolphins by changing transition probabilities, bout durations and the time taken to return to a behavioural state once disrupted. Both diving (inferred foraging) and travelling were significantly disrupted by vessel interactions. The addition of one of more vessels during an encounter further disrupted diving. Responses of Hector’s dolphins to swim attempts were assessed from commercial tourism vessel trips (n = 420). The method of approach and swimmer placement affected the dolphins’ behaviour, with a reduction in avoidance when regulations were adhered to, i.e. using line abreast and around methods. Dolphin responses to swim encounters were also correlated with the number of successive attempts, dolphin group size and initial behaviour. Although Hector’s dolphins appear to be more tolerant of the presence of swimmers over time, some level of sensitisation to seasonally high levels of vessel interactions was also detected. The effects of swim encounters could potentially be exacerbated by the use of stones as an auditory stimulant. Specifically, swimmers who used stones had a greater probability of close and sustained approaches by dolphins than those who sang or simply floated on the surface of the water. Based on opportunistic photo-identification surveys (n = 254), 46% and 44% of the 50 identifiable individuals were infrequently and occasionally recorded interacting with commercial tourism vessels, respectively. It was also estimated that individuals using Akaroa Harbour are exposed to the highest level of cetacean-based tourism in New Zealand. This implies that dolphins that are frequent users of the harbour are likely to be more exposed to intensive tourism pressure. The high resighting rate of some individuals further suggests that frequent users are unlikely to discontinue using the harbour, even though they face increased human disturbance. Data presented here reveal the nature and the susceptibility of Hector’s dolphins to tourism activities, warranting the continuation of a moratorium on new permits. Furthermore, a reduction in daily trip numbers should be considered. Ongoing monitoring of this population’s response to tourism activities, combined with an integrated and adaptive approach to management, gives the best chance of ensuring the sustainability of the industry.
Keywords: Dolphin behaviour; Ecotourism; Effects of tourism